Squamous Cell Carcinoma - Hallmark and Treatment Modalities 2020
DOI: 10.5772/intechopen.86041
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Force and Actin Dynamics during Cutaneous Squamous Cell Carcinoma (cSCC) Progression: Opportunities for Novel Treatment Modalities

Abstract: Cutaneous squamous cell carcinoma (cSCC) accounts for 25% of cutaneous malignancies diagnosed in the Caucasian population. Surgical removal in combination with radio-and chemotherapy is an effective treatment; however, prognosis for patients suffering from aggressive cSCC is still relatively poor. Increasing prevalence coupled with high mortality and morbidity in aggressive metastatic forms of cSCC highlights the need for development of novel targeted therapeutics. Metastasis is a complex process requiring dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…43 SCC-9 cells also have actin filaments and are used to study the various parameters of actin-related diseases. 44 Hence, these cell lines are best to study the dye related to actin binding. 45,46 Takagi et al recently developed an F-actin-binding dye, named HMRef, on the HeLa cell line.…”
Section: ■ Discussionmentioning
confidence: 99%
“…43 SCC-9 cells also have actin filaments and are used to study the various parameters of actin-related diseases. 44 Hence, these cell lines are best to study the dye related to actin binding. 45,46 Takagi et al recently developed an F-actin-binding dye, named HMRef, on the HeLa cell line.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Another pathway by which CSPG4 enhances integrin activity is through intracellular signalling involving Cdc42 (a member of the Rho family of GTPases), the activated-Cdc42-associated kinase-1 (Ack1) and p130cas [ 83 ], all of which have been shown to be critical in transmitting mechanical forces and managing actin dynamics governing SCC development and progression [ 100 , 101 ]. Clustering of CSPG4 has been shown to activate Cdc42 to a GTP-conjugated state.…”
Section: Structure and Function Of Cspg4mentioning
confidence: 99%
“…Another pathway by which CSPG4 enhances integrin activity is through intracellular signalling involving Cdc42 (a member of the Rho family of GTPases), the activated-Cdc42-associated kinase-1 (Ack1) and p130cas [83], all of which have been shown to be critical in transmitting mechanical forces and managing actin dynamics governing SCC development and progression [101,102]. Clustering of CSPG4 has been shown to activate Cdc42 to a GTP-conjugated state.…”
Section: Cspg4 and Integrin Signallingmentioning
confidence: 99%
“…Furthermore, at least one study has shown that CSPG4-mediated activation of integrin enhances resistance to chemotherapy by sustained activation of the AKT pathway via PI3K [81]. The role of CSPG4 in modulating the cytoskeleton makes it an ideal target of modern anticancer research, given the current interest in proteins involved in regulating mechanical forces and actin dynamics [102].…”
Section: Cspg4 and Integrin Signallingmentioning
confidence: 99%